A Deconvolution Approach to the Three Dimensional Identification of Cracks in Magnetic Slabs - Amr A. Adly; Salwa K. Abd-El-Hafiz (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Nondestructive assessment of cracks in metallic parts has always been a topic of industrial interest. In the past, different approaches have been proposed to assess such cracks. Recently, semi-orthogonal compactly supported spline wavelets were utilized to efficiently identify the 3D spatial location of cracks in conducting slabs of finite thicknesses. Within this proposed approach a horizontally oriented field sensor is employed on top of a magnetic slab subject to uniform horizontal magnetic field. In this paper the 3D spatial identification of cracks in conducting slabs is carried out through the Fourier transform by de-convoluting sensor response. In comparison to the previously adopted approach, the approach proposed in this paper is capable of identifying cracks that span over a relatively larger distance.  Details of the crack detection methodology and simulations are given in the paper.